Early Childhood Education: Integrative Holistic Early Childhood Development Program Implementation - Apriyansyah, Chandra; Awaluddin Tjalla; Ari Saptono; Hartati, Sofia; Jalal, Fasli; Sukatmi, Sri; Ismail , Mazeni; Lia Kurniawaty (Universitas Nahdlatul Ulama Surabaya, 2024)
This study aims to observe how the Integrative Holistic Early Childhood Development Program is implemented in ECCE units. The survey's conclusion that Bogor Regency's use of Integrative Holistic ECCE is still subpar served as the impetus for this investigation. This study uses a descriptive, qualitative research design. The PAUD unit in Bogor Regency hosted the study for three months, from March to May 2024. This study includes principals and instructors as subjects. Qualitative descriptive analysis is the data analysis method that is applied. Data reduction, data visualization, conclusion drafting, and data verification are among the stages of data analysis. Using triangulation, the data's veracity is verified. According to the study's findings, principals and teachers have a positive attitude toward PAUD HI, employ effective strategies or methods in their programs, and work together with the government, non-governmental organizations, parents, and the private sector. However, one of the main challenges in putting PAUD HI programs into practice in ECCE units is the lack of funding, facilities, and teaching staff, as well as a lack of resources for the learning environment and parent involvement. The study's conclusion The Integrative Holistic Early Childhood Development (PAUD HI) program faces a number of obstacles during implementation. To overcome these obstacles, the community, government, and educational institutions must work together well, actively involve parents, improve infrastructure and human resources, and conduct periodic evaluations.